Evaluasi Implementasi Kurikulum Merdeka Belajar di SMPN 1 Buduran Dalam Perspektif Guru dan Siswa - Satunggale Kurniawan; Nila Dewi Wahyuningsih (Paidagogia: Jurnal Pengajaran dan Pendidikan, 2025)
This study examines the implementation of the Merdeka Curriculum at SMPN 1 Buduran from the perspectives of teachers and students. Aiming to foster contextual, flexible, and student-centered learning, the research utilized a descriptive qualitative approach, gathering data through interviews with 10 teachers and 32 students, classroom observations, and school document analysis. The findings show that 80% of teachers appreciate the curriculum's flexibility in designing learning tailored to student needs, while 70% have successfully integrated project-based learning and group discussions. However, 60% still face challenges in creating authentic assessments aligned with the curriculum's principles. From the students' viewpoint, 65% report feeling more engaged in their learning, yet 50% struggle to understand material independently without direct teacher guidance. Key obstacles include limited facilities, unstable internet access, and inadequate technological resources. The principal stresses the need for further teacher training, particularly in competency-based assessments. In summary, while the Merdeka Curriculum's implementation at SMPN 1 Buduran demonstrates progress in enhancing participation and flexibility, addressing facility improvements and strengthening teacher capacity is essential for achieving its full potential.